Optical properties of superconducting EuFe2 (As1‐xPx)2. Issue 1 (28th June 2016) - Neubauer, David; Pronin, Artem V.; Zapf, Sina; Merz, Johannes; Jeevan, Hirale S.; Jiao, Wen‐He; Gegenwart, Philipp; Cao, Guang‐Han; Dressel, Martin
Abstract: We present a broadband optical‐conductivity study of superconducting single‐crystalline EuFe 2 (As 1 − x P x ) 2 with three different substitutional levels. We analyze the normal‐state electrodynamics by decomposing the conductivity spectra using a Drude–Lorentz model with two Drude terms representing two groups of carriers with different scattering rates. The analysis reveals that the scattering rate of at least one of the Drude components develops linearly with temperature for each doping level. This points toward strong electron–electron correlations and a non‐Fermi‐liquid behavior in the P‐substituted superconducting Eu‐122 pnictides. We also detect a transfer of the spectral weight from mid‐infrared to higher frequencies and assign it to the Hund's‐rule coupling between itinerant and localized carriers. The conductivity spectra below the superconducting transition show no sharp features to be associated with the dirty‐limit superconducting s‐wave gaps. We interpret these results in terms of clean‐limit superconductivity in EuFe 2 (As 1 − x P x ) 2 . The best parametrization fit can be achieved using a two‐gap model. We find that the larger gap at the hole pockets of the Fermi surface is likely to be isotropic, while the smaller gap at the electron pockets is anisotropic or even nodal. Schematic phase diagram of EuFe 2 (As 1 − x P x ) 2 . The indicated phases are: spin density wave (SDW), superconductivity (SC), magnetic ordering of Eu spins ( T N, Eu, brown), and a spin‐glass state of the Eu subsystem ( T SG, Eu, green). Above the SC dome, a non‐Fermi‐liquid behavior (NFL) points toward a possible quantum critical point (QCP). The black arrows indicate the approximate positions of the compositions investigated in this study.